Susceptibility of ECE1 polymorphisms to Hirschsprung's disease in southern Chinese children - Lan, Chaoting; Liu, Yanqing; Wu, Xiao; Wang, Bingtong; Xin, Songqing; He, Qiuming; Zhong, Wei; Liu, Zipeng (Frontiers in Pediatrics, 2022)
Background Hirschsprung's disease (HSCR) is currently considered to be a congenital gastrointestinal malformation caused mainly by genetic factors. Endothelin Converting Enzyme-1 (ECE1) has been reported to be associated with HSCR. However, the relationship between ECE1 single nucleotide polymorphism (SNP) rs169884 and HSCR in the southern Chinese population remains unknown. Methods 1,470 HSCR patients and 1,473 controls from a southern Chinese population were recruited. The intronic SNP rs169884 in ECE1 was genotyped in all samples. We tested the association between rs169884 and HSCR under various genetic models. We also evaluated the effect of rs169884 on HSCR subtypes, including short-segment HSCR (S-HSCR), long-segment HSCR (L-HSCR) and total colonic aganglionosis (TCA). External epigenetic data were integrated to investigate the potential biological function of rs169884. Results Chromatin states data from derived neuron cells or fetal colon tissue revealed that rs169884 might control ECE1 expression through regulating its enhancer function. We did not find a significant association between rs169884 and HSCR. For HSCR subtypes, although no significant associations were detected between rs169884 and S-HSCR (OR = 1.00, 95% CI: 0.89∼1.12, Padj = 0.77) or TCA (OR = 1.00, 95% CI: 0.72∼1.38, Padj = 0.94), we found that rs169884 could increase the risk of L-HSCR (OR = 1.23, 95% CI 1.02∼1.45, Padj = 0.024). Conclusion These results suggested that rs169884 might play a regulatory role for ECE1 expression and increase susceptibility of L-HSCR in southern Chinese children.